Social networks in organizations - Vargas-Hernández, José G.; Morales-del-Rio, Cecilia (Organicom, 2019)
Social networks play a key role in communication-related organizations. Unfortunately, the current literature has only been focused on the use of social networks within communities for creation and interaction between the organization and consumers, concerning mostly digital marketing and branding. Much of this literature falls under two interesting perspectives, the importance of communication in organizations and the use of social networks as a new communication channel. Organizations need communication as part of the understanding between management and employees, whereas social networks integrate agents into digital communities. This study summarizes the literature concerning each of these perspectives to derive assumptions and expected results on communication with social networks within organizations. Then, by means of a sociological perspective, the reconciliation of these views considering the incorporation of social networks as a new form of internal communication for organizations is proposed. There is a need for integration of communities with social networks, based on the context of premises made by previous studies.